2014
DOI: 10.1515/prilozi-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemia-Driven Optimal Therapeutic Approach in Asymptomatic Patients with High Cardiovascular Risk: The Value of Clinical, Laboratory and Myocardial Spect Imaging Findings

Abstract: Background: We wanted to evaluate the presense of myocardial ischaemia in asymptomatic patients with high cardiovascular risk, the influencing clinical and laboratory factors and the impact of ischaemia on final management decision.Material and methods: We evaluated 60 asymptomatic patients with high CV risk, who underwent SPECT myo-cardial perfusion imaging (MPI) for detection of suspected CAD. We used the 17 segment model for quantitative and semiquantitative scan perfusion and function analysis using perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…We had confirmed the impact of myocardial ischaemia detected by MPI on management decision in high-risk asymptomatic patients in our previous study. 19 The study showed that type 2 diabetic patients without a history of CAD and normal MPI have a relatively good 2-year prognosis. We found four false-positive results of MPI (4 of 12 had myocardial perfusion abnormalities with normal coronary angiography).…”
Section: Discussionmentioning
confidence: 91%
“…We had confirmed the impact of myocardial ischaemia detected by MPI on management decision in high-risk asymptomatic patients in our previous study. 19 The study showed that type 2 diabetic patients without a history of CAD and normal MPI have a relatively good 2-year prognosis. We found four false-positive results of MPI (4 of 12 had myocardial perfusion abnormalities with normal coronary angiography).…”
Section: Discussionmentioning
confidence: 91%